Various CSR practices PT. Grab Indonesia during the Covid-19 Pandemic - putri, Putri Sekar Diani (Universitas Ahmad Dahlan, 2022)
The covid-19 virus has shocked the world, the number of deaths due to the very fast spread of the covid-19 virus, the covid-19 virus first spread in Wuhan, China at the end of December. The COVID-19 pandemic in Indonesia continues to increase. As a result, countries in the world have implemented several regulations to prevent the spread of the virus. In Indonesia itself, several regions/regions are locked down, or work from home. Situations like this affect many sectors of life, from education to the economy. The social responsibility of a company or better known as CSR has become a topic of discussion among the public and business people. PT. Grab Indonesia as an Indonesian online transportation application together with the government carried out the Covid-19 vaccination as an implementation of CSR in the New Normal era of the Covid-19 pandemic in several regions in Indonesia for the elderly and online transportation drivers. This study aims to determine CSR programs to help PT. Grab Indonesia in accelerating the handling of COVID-19. . Corporate Social Responsibility (CSR) is a commitment from the company to make a long-term contribution as a manifestation of business ethics to certain issues in society or the environment to create better conditions and environment around the company. This paper will explain what efforts are being made by companies through their CSR programs to help overcome this Covid-19 pandemic. This study uses a qualitative approach with descriptive analysis method. a research method by collecting data according to the truth then the data is compiled, processed and analyzed to be able to provide an overview of the main problems at PT.Grab Indonesia.